Economic growth is a double-edged sword for nutrition - Vivalo, Julia (International Food Policy Research Institute, 2013)
To achieve real nutrition gains from economic growth, policymakers have to tackle nutrition on all fronts and at all levels -- from making social protection, agriculture, and other programs more nutrition-sensitive to providing an environment in which such programs can flourish.